Harbinets in Kharkov (in memory of the philologist and sinologist V. V. Levitsky) - Глибицька, Світлана Борисівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Harbinets in Kharkov (in memory of the philologist and sinologist V. V. Levitsky)